Nominal exchange rate regimes and relative price dispersion: On the importance of nominal exchange rate volatility for the width of the border - Günter W. Beck (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
Based on a broad set of regional aggregated and disaggregated consumer price index (CPI) data from major industrialized countries in Asia, North America and Europe we are examining the role that national borders play for goods market integration. In line with the existing literature we find that intra-national markets are better integrated than international market. Additionally, our results show that there is a large 'ocean' effect, i.e., intercontinental markets are significantly more segmented than intra-continental markets. To examine the impact of the establishment of the European Monetary Union (EMU) on integration, we split our sample into a pre-EMU and EMU sample. We find that border effects across EMU countries have declined by about 80% to 90% after 1999 whereas border estimates across non-EMU countries have remained basically unchanged. Since global factors have affected all countries in our sample similarly and major integration efforts across EMU countries were made before 1999, we suggest that most of the reduction in EMU border estimates has been 'nominal'. Panel unit root evidence shows that the observed large differences in integration across intra- and inter-continental markets remain valid in the longrun. This finding implies that real factors are responsible for the documented segmentations across our sample countries.
urn:nbn:de:hebis:30-10498
Keywords: F02; F40; F41; 330; Real exchange rate dispersion; real and nominal border effect; goods market integration; nominal exchange rate regime neutrality; Kaufkraftparität; Internationaler Preiszusammenhang; Grenze; Marktintegration; Wechselkurssystem; Europäische Wirtschafts- und Währungsunion; EU-Staaten